Synthesis and photophysics of new benzophenoxazine derivatives fused with julolidine - Raju, B. Rama (2014)
Phenoxazinium salts are mostly used as markers for various purposes. In this context, we report the synthesis of five new benzophenoxazinium derivatives fused with julolidine moiety. These benzophenoxazinium chlorides were obtained by the condensation of anthracen-1-amine, naphthalen-1-amine, N-phenylnaphthalen-1-amine, N-propylnaphthalen-1-amine and 3-(naphthalen-1-ylamino)propan-1-ol, with 9-nitroso-8-hydroxyjulolidine hydrochloride as blue solids. The photophysical behavior of these compounds in anhydrous ethanol when acidified with TFA or basified with TEAH was also investigated as well as their response in aqueous media.